Emotional intelligence leadership and career decision-making self-efficacy among college students in China: The mediating role of social support and proactive personality - Kaida Wang; Jun Hu; Xiao Yang; Hua Ding; Hailun Huang; Zhanlu Xu (PLoS ONE, 2026)
Student leadership education is a significant component of global education that positively impacts college students’ employment. This study examined the relationship between emotional intelligence leadership and career decision-making self-efficacy, specifically investigating the mediating roles of social support and proactive personality. A cross-sectional survey was conducted among 996 university students in China (314 males, 682 females, aged 18 to 23) using the Emotional Intelligence Leadership Scale, Career Decision-Making Self-Efficacy Scale, Social Support Scale, and Proactive Personality Scale. Structural equation modeling revealed that emotional intelligence leadership was significantly and positively correlated with career decision-making self-efficacy. Furthermore, social support and proactive personality mediated this relationship through three distinct pathways: independent mediation by social support, independent mediation by proactive personality, and a serial mediation involving both factors. These findings contribute to the understanding of how emotional intelligence leadership facilitates career development. Educational institutions are encouraged to enhance emotional intelligence leadership education and foster supportive social environments to bolster students’ career decision-making self-efficacy.